Development of a Novel Brief Quantitative Sensory Testing Protocol That Integrates Static and Dynamic Pain Assessments: Test-Retest Performance in Healthy Adults. Issue 2 (2nd October 2021) - De Vita, Martin J; Buckheit, Katherine; Gilmour, Christina E; Moskal, Dezarie; Maisto, Stephen A
Abstract: Objective: Quantitative sensory testing is an expanding pain research domain with numerous clinical and research applications. There is a recognized need for brief reliable quantitative sensory testing protocols that enhance assessment feasibility. This study aimed to integrate static (pain threshold, tolerance, suprathreshold) and dynamic (conditioned pain modulation, offset analgesia, temporal summation) pain reactivity measures into a brief 20-minute protocol that uses a single portable device. The test-retest performance of this optimized protocol was evaluated. Design: Using a test-retest design, the brief quantitative sensory testing assessment was administered to participants on two occasions separated by exactly 7 days. Setting: A clinical psychology research laboratory at Syracuse University. Subjects: Participants were 33 healthy adults recruited from Syracuse University's online research participation pool. Methods: A portable computerized quantitative sensory testing device delivered contact-heat pain to assess static and dynamic pain measures in participants. Dynamic responses were continuously recorded using a computerized visual analog scale. Results: Pain threshold, tolerance, and suprathreshold exhibited excellent reliability (intraclass correlations ranged from 0.80 to 0.83). Conditioned pain modulation, offset analgesia, temporal summation yielded reliability in the good to excellent range (intraclass correlations ranged from 0.66 to 0.71). Conclusions: Findings suggested that this brief integrated QST protocol may reliably monitor human pain reactivity over brief periods. This protocol may enhance quantitative sensory testing feasibility in clinical and research settings.